Gambaran Pengetahuan Ibu tentang Malnutrisi pada Balita di Posyandu Dukuh Kendal Desa Sidodadi Kecamatan Sukosewu Kabupaten Bojonegoro tahun 2014 - Siti Patonah, Siti Patonah (Jurnal Penelitian Kesehatan, 2014)
Â Â Â Â Â Â Â Â Â Â  MalnutritionÂ  is still a major problem in infants. Along with the times, malnutrition is still a major problem in infants. The high rate ofÂ Â  malnutrition is influenced by several factors such as low levelsÂ  ofÂ  education Â (knowledge)Â  aboutÂ  the importance of maternal nutrition intakeÂ  asÂ  long asÂ  theÂ  child Â isÂ  still Â Â in Â Â the Â processÂ  of Â grow and develop. The condition of infants who came to Kendal Â IHC Â there are toddler body weight under Red lines on the KMS. Â Â Â Â Â Â Â Â Â Â  The method used in this study was a descriptive survey approach.Variable in this study is theÂ  mothersÂ  knowledgeÂ  aboutÂ  malnutrition in children under five in Village Kendal Sidodadi, Sukosewu District, Bojonegoro regency. The Â population Â inÂ  this study wereÂ  allÂ  mothersÂ  with Â children Â Â underÂ  five Â in village of Â Kendal Â Sidodadi, Â Sukosewu District ,Bojonegoro regency, amount 158 respondents and the sample was motherâs with toddlers who came to IHC Village Kendal, Sidodadi District,BojonegoroÂ  regency totaled 109 respondents, the sampling used in purposive sampling. Data were collected by using a questionnaire later on though by way ofÂ  editing, Â coding, Â scoring Â then Â tabulated Â and Â presented Â in Â the Â form Â of Â percentages wereÂ Â Â Â Â  analyzed with descriptive analysis. Â Â Â Â Â Â Â Â Â  The results showed that more than a majority of the respondents or mothers have good knowledge of malnutrition in children under five is 56 respondents (51.37%) of the 109 respondents. Â Â Â Â Â Â  Â Mothers knowledgeÂ  about malnutrition in under-five is good ,good Â motherâs knowledge would Â be Â useful if Â supported by the attitude and behavior of a true mother in feeding infants,Â Â Â Â  Â so that children will not experience malnutrition. Keywords: Motrerâs,Knowledge , MalnutritionÂ Â